LIGHT DETECTION AND RANGING DEVICE USING COMBINED PULSE AND CONTINUOUS OPTICAL SIGNALS (2021)
The subject matter of this specification relates to a light detection and ranging (LiDAR) device that comprises, in some implementations, a pulsed-laser source configured to generate a pulsed optical signal, a continuous wave (CW) laser source configured to generate a CW optical signal, one or more optical amplifier circuits configured to amplify at least the pulsed optical signal, a combiner configured to combine the pulsed optical signal and the CW optical signal into a hybrid transmission signal, and at least one photodetector configured to receive a reflection signal produced by reflection of the hybrid transmission signal by a target.